Behavioral Assessment of Sensory, Motor, Emotion, and Cognition in Rodent Models of Intracerebral Hemorrhage - Shi, Xiaoyu; Bai, Huiying; Wang, Junmin; Wang, Jiarui; Huang, Leo; He, Meimei; Zheng, Xuejun; Duan, Zitian; Chen, Danyang; Zhang, Jiaxin; Chen, Xuemei; Wang, Jian (Frontiers in Neurology, 2021)
Intracerebral hemorrhage (ICH) is the second most common type of stroke and has one of the highest fatality rates of any disease. There are many clinical signs and symptoms after ICH due to brain cell injury and network disruption resulted from the rupture of a tiny artery and activation of inflammatory cells, such as motor dysfunction, sensory impairment, cognitive impairment, and emotional disturbance, etc. Thus, researchers have established many tests to evaluate behavioral changes in rodent ICH models, in order to achieve a better understanding and thus improvements in the prognosis for the clinical treatment of stroke. This review summarizes existing protocols that have been applied to assess neurologic function outcomes in the rodent ICH models such as pain, motor, cognition, and emotion tests. Pain tests include mechanical, hot, and cold pain tests; motor tests include the following 11 types: neurologic deficit score, modified neurologic severity score, corner test, staircase test, rotarod test, cylinder test, grid walk test, forelimb placing test, wire hanging test, beam walking test, and horizontal ladder test; learning and memory tests include Morris water maze, Y-maze, and novel object recognition test; emotion tests include elevated plus maze, sucrose preference test, tail suspension test, open field test, and forced swim test. This review discusses these assessments by examining their rationale, setup, duration, baseline, procedures as well as comparing their pros and cons, thus guiding researchers to select the most appropriate behavioral tests for preclinical ICH research.